The quality of Syrian healthcare services during COVID-19: A HEALTHQUAL approach - Lilas Allahham; Sulaiman Mouselli; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Mihajlo Jakovljevic (Frontiers Media S.A., 2022)
Syria is a developing country that face enormous healthcare challenges that aggravated with the outbreak of COVID-19. In the study, we evaluate the perceived healthcare service quality based on hospital type, public and private, using five HEALTHQUAL dimensions. We find that service quality in Syrian private hospitals is perceived better that in public hospitals. However, neither type of hospitals scores exceptionally high in any of the examined HEALTHQUAL dimensions. On the contrary, both hospitals score extremely low in the Improvement dimension. We argue that crowdedness environment, medical staff availability and their low salaries, pricing policies as well as the health insurance system, are to blame for such low perceived quality.